Utility of Routine Genomic Sequencing for Infection Control Surveillance. (4th October 2017) - Ellison, Richard T; Hoss, Andrew; Mathew, Jomol; Halperin, Jeff; Gross, Brian; Ward, Doyle V
Abstract: Background: Recent work indicates that comprehensive genomic sequencing can be a highly effective tool in defining the transmission of microbial pathogens. We have studied the utility of the routine use of genomic sequencing for infection control surveillance in an academic medical center. Methods: The genomes of inpatient and emergency department isolates of Staphylococcus aureus, Pseudomonas aeruginosa, Klebsiella pneumoniae, and Enterococcus faecium were sequenced. Within each species, single-nucleotide polymorphisms (SNP) were identified in the core genome for all isolates using alignment-based methods. The number of SNP differences between isolate pairs was determined and used, in combination with the patient's electronic medical records to identify potential transmission events. Results: Between September 2016 and March 2017, 388 S. aureus, 66 P. aeruginosa, 48 K. pneumoniae, and 29 E. faecium isolates were sequenced from 373 patients. There was variation in the distribution of SNP differences between intrapatient isolates for the four pathogens; with the least variability for E. faecium and greatest for P. aeruginosa . The majority of the bacterial isolates from separate patients appeared to be genetically unique exhibiting marked SNP differences from other isolates. There were 19 sets of isolates where the SNP variation between interpatient isolates was either comparable to that of intrapatient variation (12) and suggestive of recent transmission events, or with SNP variation somewhat greater than the intrapatient SNP variation (7) suggesting relative relatedness. Only one of the highly related sets had been previously identified by standard infection control surveillance. Likely transmissions appeared to have occurred both in the inpatient and outpatient settings, and the transmission routes were not always apparent. Conclusion: The routine use of genomic sequencing analysis identified previously unrecognized likely transmission events within the institution's patient population that are of relevance to infection control surveillance. This capacity should significantly enhance our understanding of the epidemiology of hospital acquired infections, and assist in developing and implementing new prevention strategies. Disclosures: R. T. Ellison III, Philips Healthcare: Consultant and Grant Investigator, Consulting fee and Research grant; A. Hoss, Philips: Employee, Salary; J. Mathew, Philips Healthcare: Investigator, Research grant; J. Halperin, Philips Healthcare: Employee and Shareholder, Salary; B. Gross, Philips: Employee and Shareholder, Salary; D. V. Ward, Philips Healthcare: Consultant, Investigator and Research Contractor, Consulting fee, Research support and Salary